2009
DOI: 10.5539/ijbm.v4n4p140
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Consumer Decision-Making Styles of Young-Adults in Malaysia

Abstract: The purpose of this exploratory study was to investigate the consumer decision-making styles of young-adults in Malaysia. Exploratory factor analysis was conducted to determine the dimensions considered by young-adults in their transactions in the market. Seven reliable factors and their corresponding decision-making styles were identified: Novelty, Brand Conscious Consumer; Perfectionistic, High-Quality Conscious Consumer; Confused by Overchoice; Recreational, Hedonistic Consumer; Impulsive, Careless Consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 18 publications
(47 reference statements)
1
32
1
4
Order By: Relevance
“…A recent study by Madani et al (2012) [30] on young Malaysian adults identified four factors representing their decision making styles: Novelty/Brand Consciousness; Perfectionist/High-Quality Consciousness; Recreational/Hedonistic Consciousness; and Impulsive/Careless Consumer. These results are dissimilar to those reported by Mohklis (2009) [35]; (2010) [36], and no attempt was made to identify differences between the decision making styles of the male and female respondents. Recent studies have shown that apart from gender, culture is also a strong predictor of consumer decision making styles.…”
Section: Gender Shopping Behavior and Decision Making Stylescontrasting
confidence: 57%
See 2 more Smart Citations
“…A recent study by Madani et al (2012) [30] on young Malaysian adults identified four factors representing their decision making styles: Novelty/Brand Consciousness; Perfectionist/High-Quality Consciousness; Recreational/Hedonistic Consciousness; and Impulsive/Careless Consumer. These results are dissimilar to those reported by Mohklis (2009) [35]; (2010) [36], and no attempt was made to identify differences between the decision making styles of the male and female respondents. Recent studies have shown that apart from gender, culture is also a strong predictor of consumer decision making styles.…”
Section: Gender Shopping Behavior and Decision Making Stylescontrasting
confidence: 57%
“…For instance, the CSI used by Mokhlis (2009) [35] on a Malaysian sample yielded different results due to the cultural differences, implying that CSI in its original form cannot be generalized without some modification.…”
Section: Consumer Decision Making Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are also consistent with the findings of a study conducted by Sproles and Sproles (1990), in which novelty and fashion-conscious consumers resemble a perfectionist consumer, but with the important exception that these types of consumers may also have a passive and accepting characteristic. Furthermore, novelty-seeking consumers are likely to buy best-selling brands that are the latest in style at expensive stores (Mokhlis, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Statman found that propensities for risk, regret, and maximization vary by country of origin and by gender. Furthermore, consumer decision-making styles also vary according to culture (Mokhlis, 2009). There are numerous possible factors that might cause distinct variations between sets of countries such as: culture, sociology, level of average income to name a few.…”
Section: Introductionmentioning
confidence: 99%